Sie sind auf Seite 1von 4

Double Integrations by Parts

Tae-Joon Cho
DAMTP, University of Cambridge
June 13, 2012

Trigonometric Functions - Double Integrations by Parts. An example where a double


integration by parts is used is

c
mx
s
I(m,n) = e cos nxdx,
I(m,n) = emx sin nxdx
(1)
With

u1 = emx
v10 = cos nx
u01 = memx , v1 = n1 sin nx

we find

u2 = emx ,
v20 = sin nx
u02 = memx , v2 = n1 cos nx

c
I(m,n)

c
I(m,n)

emx cos nxdx

1 mx
m
= e sin nx
emx sin nxdx
n
n



m
1 mx
m
1 mx
mx
e cos nx +
e cos nxdx
= e sin nx
n
n
n
n
1
m
m2 c
= emx sin nx + 2 emx cos nx 2 I(m,n)
n
n
n
mx n sin nx + m cos nx
+c
=e
m2 + n2

and

(2)

s
I(m,n)

s
I(m,n)

emx sin nxdx

1 mx
m
= e cos nx +
emx cos nxdx
n
n



1 mx
m 1 mx
m
mx
= e cos nx +
e sin nx
e sin nxdx
n
n n
n
1
m
m2 s
= emx cos nx + 2 emx sin nx 2 I(m,n)
n
n
n
mx m sin nx n cos nx
+c
=e
m2 + n2

(3)

t.cho@damtp.cam.ac.uk
While teaching Thomas Ron. This can also be useful for 2012 NST IB Mathematics Example Sheet 0
Q4(c) for which we need to find the Fourier series for h(x) = 1 for ln2 < x 0 and h(x) = ex 1 for 0 < x ln 2,
ln 2
ln 2
where we need to evaluate 0 ex cos nxdx and 0 ex sin nxdx.

Trigonometric Functions - Complex Representation. We can also use einx = cos nx+i sin nx.

s
c
= emx (cos nx + i sin nx) dx
+ iI(m,n)
I(m,n)

= emx einx dx

= e(m+in)x dx
1
e(m+in)x
m + in
m in
= emx 2
(cos nx + i sin nx) + c
m + n2
i
emx h
(m
cos
nx
+
n
sin
nx)
+
i
(m
sin
nx

n
cos
nx)
+c
= 2
m + n2
=

"

(4)

Hyperbolic Functions - Double Integrations by Parts. Similarly, we can consider integrals


involving hyperbolic functions.

c
mx
s
J(m,n) = e cosh nxdx,
J(m,n) = emx sinh nxdx
(5)
With

u1 = emx
v10 = cosh nx
0
mx
u1 = me , v1 = n1 sinh nx

we find

u2 = emx ,
v20 = sinh nx
0
mx
u2 = me , v2 = n1 cosh nx

c
J(m,n)
=

emx cosh nxdx

1 mx
m
e sinh nx
emx sinh nxdx
n
n



1 mx
m 1 mx
m
mx
= e sinh nx
e cosh nx
e cosh nxdx
n
n n
n
1
m
m2 c
= emx sinh nx 2 emx cosh nx + 2 J(m,n)
n
n
n
n
sinh
nx

m
cosh
nx
+ c, m 6= n
= emx
n 2 m2
=

c
J(m,n)

and

(6)

s
J(m,n)

s
J(m,n)

emx sinh nxdx

1 mx
m
= e cosh nx
emx cosh nxdx
n
n



1 mx
m 1 mx
m
mx
= e cosh nx
e sinh nx
e sinh nxdx
n
n n
n
1
m
m2 s
= emx cosh nx 2 emx sinh nx 2 J(m,n)
n
n
n
mx n cosh nx m sinh nx
+ c, m 6= n
=e
n 2 m2

(7)

Hyperbolic Functions - Sums and Differences. We could also consider

s
c
= emx (cosh nx + sinh nx)dx
+ J(m,n)
J(m,n)

= emx enx dx
1
e(m+n)x + c
m
+
n

= emx (cosh nx sinh nx)dx

= emx enx dx
=
s
c
J(m,n)
J(m,n)

1
e(mn)x + c
mn

(8)

(9)

and we find
c
J(m,n)

s
J(m,n)



1
1
1
(m+n)x
(mn)x
=
e
+
e
+c
2 m+n
mn
emx (m n)enx + (m + n)enx
=
+c
2
m2 n2
emx m(enx + enx ) n(enx enx )
+c
=
2
m2 n 2
emx 2m cosh nx 2n sinh nx
=
+c
2
m2 n2
m cosh nx n sinh nx
= emx
+c
m2 n2


1
1
1
(m+n)x
(mn)x
e

e
+c
=
2 m+n
mn
emx (m n)enx (m + n)enx
=
+c
2
m2 n2
emx m(enx enx ) n(enx + enx )
=
+c
2
m2 n 2
emx 2m sinh nx 2n cosh nx
=
+c
2
m2 n2
m sinh nx n cosh nx
= emx
+c
m2 n2

What if m = n? We have

c
J(m,n) = emx cosh mxdx,

"

(10)

"

(11)

s
J(m,n)

emx sinh mxdx

(12)

In this case, we need to resolve the hyperbolic functions into exponentials, i.e.

s
c
= emx sinh mxdx
= emx cosh mxdx
J(m,n)
J(m,n)

mx + emx
emx emx
mx e
= e
dx
= emx
dx
2
2




1
1 2mx
1 2mx
1
=
e
+x +c
=
e
x +c
2 2m
2 2m
e2mx x
e2mx x
+ +c
=
+c
=
4m
2
4m
2

(13)

We see the linear terms which cannot be obtained by integration by parts. This can also be found
by sums and differences,

s
c
= emx (cosh mx + sinh mx)dx
+ J(m,m)
J(m,m)

= e2mx dx
=
c
s
J(m,m)
J(m,m)
=

1 2mx
e
+c
2m

(14)

emx (cosh mx sinh mx)dx

dx

=x+c

(15)

and we find
e2mx 1
+ x+c
4m
2
e2mx 1
=
x+c
4m
2

c
J(m,m)
=
s
J(m,m)

"
"

(16)
(17)